The Light-Harvesting Chlorophyll a/b Binding Proteins Lhcb1 and Lhcb2 Play Complementary Roles during State Transitions in Arabidopsis . Issue 9 (5th September 2014) - Pietrzykowska, Malgorzata; Suorsa, Marjaana; Semchonok, Dmitry A.; Tikkanen, Mikko; Boekema, Egbert J.; Aro, Eva-Mari; Jansson, Stefan
Abstract : Arabidopsis lines lacking either light-harvesting complex (LHC) protein Lhcb1 or Lhcb2 were produced, revealing that Lhcb1 and Lhcb2 play different roles during state transitions and that both are necessary but neither is sufficient. Plant lacking Lhcb1 lacked most LHCII trimers but plants lacking Lhcb2 contained LHCII similar to the wild type but could not perform state transitions. Abstract: Photosynthetic light harvesting in plants is regulated by phosphorylation-driven state transitions: functional redistributions of the major trimeric light-harvesting complex II (LHCII) to balance the relative excitation of photosystem I and photosystem II. State transitions are driven by reversible LHCII phosphorylation by the STN7 kinase and PPH1/TAP38 phosphatase. LHCII trimers are composed of Lhcb1, Lhcb2, and Lhcb3 proteins in various trimeric configurations. Here, we show that despite their nearly identical amino acid composition, the functional roles of Lhcb1 and Lhcb2 are different but complementary. Arabidopsis thaliana plants lacking only Lhcb2 contain thylakoid protein complexes similar to wild-type plants, where Lhcb2 has been replaced by Lhcb1. However, these do not perform state transitions, so phosphorylation of Lhcb2 seems to be a critical step. In contrast, plants lacking Lhcb1 had a more profound antenna remodeling due to a decrease in the amount of LHCII trimers influencing thylakoid membrane structure and, more indirectly, state transitions. Although state transitions are also found in green algae, the detailed architecture of the extant seed plant light-harvesting antenna can now be dated back to a time after the divergence of the bryophyte and spermatophyte lineages, but before the split of the angiosperm and gymnosperm lineages more than 300 million years ago.